Domestication of Crop Metabolomes: Desired and Unintended Consequences. (June 2021) - Alseekh, Saleh; Scossa, Federico; Wen, Weiwei; Luo, Jie; Yan, Jianbing; Beleggia, Romina; Klee, Harry J.; Huang, Sanwen; Papa, Roberto; Fernie, Alisdair R.
Abstract : The majority of the crops and vegetables of today were domesticated from their wild progenitors within the past 12 000 years. Considerable research effort has been expended on characterizing the genes undergoing positive and negative selection during the processes of crop domestication and improvement. Many studies have also documented how the contents of a handful of metabolites have been altered during human selection, but we are only beginning to unravel the true extent of the metabolic consequences of breeding. We highlight how crop metabolomes have been wittingly or unwittingly shaped by the processes of domestication, and highlight how we can identify new targets for metabolite engineering for the purpose of de novo domestication of crop wild relatives. Highlights: Next-generation sequencing has dramatically boosted our ability to study selection during domestication and crop improvement. Domestication of our crop species is characterized by a reduction in allelic diversity and massive changes in both their gene expression and visible phenotype. An increasing number of studies suggest that metabolism is also considerably affected. However, in contrast to gene expression changes which are largely conserved, changes at the level of the metabolome appear to be species-specific.